Self-regulation: a horizon of posibilities - Portilla Candiotti, María Alexandra (2017)
Self-regulation, perceived as a cerebral function that occurs in different dimensions of human development (biological, cognitive, emotional, social and prosocial), is constituted by the ability to regulate voluntarily our behavior, thoughts and emotions. By understanding it, the opportunity to improve the capacity for learning and adaptive behavior is provided. The second decade of life is a crucial stage in the awareness of self-regulation strategies in order to respond adequately and  thereby be allowed to succeed and reach one’s goals in different contexts. All in all, it is a powerful tool to improve the quality of life of our children and adolescents that will allow them to take advantage of better opportunities throughout their lives. In the specific case of students with ADHD, it is essential to know about the characterization of students from the approach and theory of information processing that allows us to identify and understand the challenges that children and adolescents have mainly in their schools system.